Breaking the Silence: The Phenomenology of the Female High School Band Director. (October 2019) - Bovin, Amy J.
The purpose of this study was to investigate the phenomenology of the female high school band director (FHSBD). In order to achieve a sample for regional maximum variation, one FHSBD from each county in the state of Connecticut was interviewed. After gathering data from a series of three interviews, I used Moustakas's modification of the Van Kaam method to analyze data to align with common phenomenological analysis techniques. I identified the following nine themes from relevant and validated invariant constituents: (1) support, (2) resistance and barriers, (3) loving the students and loving music, (4) discrimination, (5) motherhood and time consumption, (6) building or rebuilding a program, (7) gender clubs, (8) high school wasn't the goal, and (9) administrative and leadership degrees and certification. Based on results from the analyzed data, I determined the essence of the FHSBD is most succinctly described as persistence.